Predicting lncRNA–Protein Interaction With Weighted Graph-Regularized Matrix Factorization - Sun, Xibo; Cheng, Leiming; Liu, Jinyang; Xie, Cuinan; Yang, Jiasheng; Li, Fu (Frontiers in Genetics, 2021)
Long non-coding RNAs (lncRNAs) are widely concerned because of their close associations with many key biological activities. Though precise functions of most lncRNAs are unknown, researches show that lncRNAs usually exert biological function by interacting with the corresponding proteins. The experimental validation of interactions between lncRNAs and proteins is costly and time-consuming. In this study, we developed a weighted graph-regularized matrix factorization method (LPI-WGRMF) to find unobserved lncRNA-protein interactions based on lncRNA similarity matrix, protein similarity matrix, and known lncRNA-protein interactions. We compared our proposed LPI-WGRMF method with four classical lncRNA-protein interaction prediction methods, that is, LPBNI, LPIHN, RWR, and collaborative filtering. The results demonstrate that the LPI-WGRMF method can produce high-accuracy performance, obtaining an AUC score of 0.9012 and AUPR of 0.7324. The case study showed that SFPQ, SNHG3, and PRPF31 may associate with Q9NUL5, Q9NUL5, and Q9UKV8 with the highest linking probabilities and need to further experimental validation.